Contactless measurement of muscle fiber conduction velocity—a novel approach using optically pumped magnetometers - Baier, Lukas; Brümmer, Tim; Senay, Burak; Siegel, Markus; Keleş, Ahmet Doğukan; Röhrle, Oliver; Klotz, Thomas; Noury, Nima; Marquetand, Justus (Journal of neural engineering, 2025)
Objective . Muscle fiber conduction velocity (MFCV) describes the speed at which electrical activity propagates along muscle fibers and is typically assessed using invasive or surface electromyography. Because electrical currents generate magnetic fields, propagation velocity can potentially also be measured magnetically using magnetomyography (MMG), offering the advantage of a contactless approach. Approach . To test this hypothesis, we recorded MMG signals from the right biceps brachii muscle of 24 healthy subjects (12 male, 12 female) using a linear array of seven optically pumped magnetometers (OPMs). Subjects maintained muscle force for 30 s at 20%, 40%, and 60% of their maximum voluntary contraction. Main results . In 20 subjects, propagation of MMG signals was observable. Change in polarity and signal cancellation enabled localization of the innervation zone. We estimated the MFCV for each condition by cross-correlating double-differentiated MMG signals. To validate our results, we examined whether MFCV estimations increased with higher force levels, a well-documented characteristic of the neuromuscular system. The median MFCV significantly increased with force ( p = 0.007), with median values of 3.2 m s −1 at 20%, 3.8 m s −1 at 40%, and 4.4 m s −1 at 60% across all 20 subjects. Significance . Our results establish the first measurements of magnetic MFCV in MMG using OPMs. These findings pave the way for further developments and application of quantum sensors for contactless clinical neurophysiology.